Does successful innovation require large urban areas? Germany as a counterexample - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
Popular theories claim that innovation activities should be located in large cities because of more favorable environmental conditions that are absent in smaller cities or remote and rural areas. Germany provides a clear counterexample to such theories. We argue that a main force behind the geography of innovation in Germany is the country's federal tradition that has shaped the settlement structure, the geographic distribution of universities and public research institutions, as well as local access to finance. Additional factors that may play a role in this respect are the system of education and the tax treatment of inheriting a business. We demonstrate the long-lasting effect of the historical political structure and distribution of knowledge sources on innovation activities today. We conclude that historical factors that shape the settlement structure and location of knowledge sources are of key importance for the geographic location of innovation activities.
Keywords: O31; R11; L26; 330; Innovation; patents; agglomeration economies; cities; Germany